Pembelajaran Tatap Muka Santri Pondok Pesantren Al-Hamid Jakarta Saat Pandemi Covid-19 - Jibril Wahyu Mahardhika (Universitas Al-Amien Prenduan, 2021)
ABSTRAKThe emergence of the Covid-19 pandemic has resulted in several educational institutions in Indonesia deciding to stop face-to-face learning and be replaced by carrying out online learning. However, Al-Hamid Islamic Boarding School Jakarta is one of the Islamic boarding schools that continues to carry out face-to-face learning during the Covid-19 pandemic. This article aims to describe the implementation of face-to-face learning in the midst of the Covid-19 pandemic, the impact of face-to-face learning in the midst of a pandemic and face-to-face learning activities in the midst of the Covid-19 pandemic at the Al-Hamid Islamic Boarding School, East Jakarta. This study uses a qualitative approach through qualitative descriptive methods with descriptive analysis of the data obtained through observation and interviews, the data sources were obtained from the principal, teachers, head of the boarding school, ustadz Al-Hamid Islamic boarding school. Face-to-face Learning in the Middle of the Covid-19 Pandemic at Al-Hamid Islamic Boarding School was carried out by changing classes and reducing the duration of learning so that it had an impact on adding activities outside the classroom, but parents benefited because their children still received learning safely. And the classroom atmosphere becomes more active and gets direct learning interactions.